Targeting a hidden site on class A beta-lactamases - SARIYAR AKBULUT, BERNA; ALTINIŞIK KAYA, FATMA ECE; SAYAR, NİHAT ALPAGU (ELSEVIER SCIENCE INC, 2018)
Increasing resistance against available orthosteric beta-lactamase inhibitors necessitates the search for novel and powerful inhibitor molecules. In this respect, allosteric inhibitors serve as attractive alternatives. Here, we examine the structural basis of inhibition in a hidden, druggable pocket in TEM-1 betalactamase. Based on crystallographic evidence that 6-cyclohexyl-1-hexyl-beta-D-maltoside (CYMAL-6) binds to this site, first we determined the kinetic mechanism of inhibition by CYMAL-6. Activity measurements with CYMAL-6 showed that it competitively inhibits the wild type enzyme. Interestingly, it exhibits a steep dose -response curve with an IC50 of 100 mu M. The IC50 value changes neither with different enzyme concentration nor with incubation of the enzyme with the inhibitor, showing that inhibition is not aggregation -based. The presence of the same concentrations of CYMAL-6 does not influence the activity of lactate dehydrogenase, further confirming the specificity of CYMAL-6 for TEM-1 beta-lactamase. Then, we identified compounds with high affinity to this allosteric site by virtual screening using Glide and Schrodinger Suite. Virtual screening performed with 500,000 drug like compounds from the ZINC database showed that top scoring compounds interact with the hydrophobic pocket that forms between H10 and Hll helices and with the catalytically important Arg244 residue through pi -cation interactions. Discovery of novel chemical scaffolds that target this allosteric site will pave the way for a new avenue in the design of new antimicrobials. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Beta-lactamase; Inhibition; Allostery; CYMAL-6; Docking; Virtual screening; ALLOSTERIC SITE; ACTIVE-SITE; PROTEIN; INHIBITORS; GENERATION; RESISTANCE; DISCOVERY; DOCKING; GLIDE